2021
DOI: 10.3389/fped.2021.598276
|View full text |Cite
|
Sign up to set email alerts
|

Motor Development in Children With Autism Spectrum Disorder

Abstract: Objective: This study was conducted to determine the gross and fine motor profiles of children with autism spectrum disorder compared to typically developing children. Additionally, we also assessed if the motor delay was more pronounced with increasing age.Method: This was a retrospective study involving children aged 12–60 months of age comparing motor development in children with autism spectrum disorder with typically developing children. Their developmental profile was assessed using Schedule of Growing S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…On the other hand, caregivers from the 2020 sample were least likely to endorse behavior difficulties and medical and gross motor concerns as first developmental concerns. This could be explained by ASD diagnostic criteria since, despite aggression, medical conditions, and gross motor delays being commonly co-occurring conditions ( 46 ), they are not required to meet an ASD diagnosis ( 47 , 48 ). Our results seem to imply an attunement in identifying ASD core characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, caregivers from the 2020 sample were least likely to endorse behavior difficulties and medical and gross motor concerns as first developmental concerns. This could be explained by ASD diagnostic criteria since, despite aggression, medical conditions, and gross motor delays being commonly co-occurring conditions ( 46 ), they are not required to meet an ASD diagnosis ( 47 , 48 ). Our results seem to imply an attunement in identifying ASD core characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges and limitations: One limitation of using MEA is that it may be challenging to perform motion tracking for multiple individuals at once [36,93] because the ROIs are likely to overlap, particularly when the target agents are located near each other. It can be addressed using either multiple cameras or methods of simultaneous tracking segmentation of different body parts in a bottom-up fashion [94].…”
Section: Study Design Andmentioning
confidence: 99%
“…A major difficulty for the design of technologies to support autistic people is the large variations in the difficulties they face [95]. If, as suggested by recent research [27,94], difficulties with motor skills contribute to explain difficulties in other domains and could impact their severity, then systems supporting synchronous motor activities with a facilitator could improve the support offered to many in this group. Large scale systems are ideally suited for this purpose, and systems like MEA could be used as a standardised tool to compare the impact of different designs on interactional synchrony and ultimately relate it to gains in the area of motor skills.…”
Section: Implications For the Design Of Systems To Support Interactio...mentioning
confidence: 99%
“…As mentioned, the main symptoms of ASD are focused on those described in diagnostic manuals [ 5 , 26 ]. However, for some time now, motor performance has been the subject of different studies because motor difficulties are observed both in fine [ 27 , 28 ] and gross motor skills and coordination [ 29 ], showing difficulties or delays in acquiring motor milestones or fundamental movement skills [ 30 , 31 ]. Children and adolescents with ASD have issues using the sensory inputs necessary for adequate postural control [ 32 ], which is essential for standing, walking, and performing activities of daily living [ 33 ].…”
Section: Introductionmentioning
confidence: 99%